1998
DOI: 10.3354/dao034045
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the fumagillin analog TNP-470 for Nucleospora salmonis and Loma salmonae infections in chinook salmon Oncorhynchus tshawytscha

Abstract: Efficacy of the fumagillin analog TNP-470 forNucleospora salmonis and Loma salmonae infections in chinook salmon Oncorh ynch us tsha wytscha 'Department of Fisheries and Oceans, Pacific Biological Station, Nanaimo, British Columbia V9R 5K6, Canada *~e p a r t m e n t of Pathology, Albert Einstein College of Medicine, Bronx, New York 10461, USA ABSTRACT: Oral treatment with fumagillin is effective for controlling various inicrosporean and myxosporean infections in fish. We tested a synthetic analog of fumagilli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 1 publication
(2 reference statements)
0
21
0
Order By: Relevance
“…TNP-470 and FOS68, inhibit the in vitro growth of Encephalitozoon hellem, E. cuniculi, E. intestinalis and other microsporidia at concentrations as low as 3 nM (Didier 1997, Didier et al 1998, Coyle et al 1998, Weiss et al 2001). In addition, both fumagillin and TNP-470 have demonstrated activity in murine and fish models of microsporidiosis (Coyle et al 1998, Higgins et al 1998. Fumagillin has also been demonstrated to have efficacy in human infection with E. hellem (ocular disease) and E. bieneusi (intestinal disease) (Molina et al 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TNP-470 and FOS68, inhibit the in vitro growth of Encephalitozoon hellem, E. cuniculi, E. intestinalis and other microsporidia at concentrations as low as 3 nM (Didier 1997, Didier et al 1998, Coyle et al 1998, Weiss et al 2001). In addition, both fumagillin and TNP-470 have demonstrated activity in murine and fish models of microsporidiosis (Coyle et al 1998, Higgins et al 1998. Fumagillin has also been demonstrated to have efficacy in human infection with E. hellem (ocular disease) and E. bieneusi (intestinal disease) (Molina et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Several laboratories have demonstrated in vitro that this drug has activity against both Encephalitozoonidae and Vittaforma corneae (Shadduck 1980, Franssen et al 1995, Didier 1997, Coyle et al 1998. TNP-470, a fumagillin derivative developed as an anti-angiogenesis drug, is active both in vitro and in vivo against several microsporidia (Coyle et al 1998, Higgins et al 1998. Fumagillin has been demonstrated to have efficacy for the treatment of diarrhoea due to E. bieneusi in AIDS patients (Molina et al 2002).…”
mentioning
confidence: 99%
“…It has also been demonstrated that TNP-470 is highly active against Encephalitozoon cuniculi and Encephalitozoon hellem , both in vitro and in vivo (Coyle and others 1998). Additionally, TNP-470 was found to inhibit the replication of N salmonis and L salmonae in salmonid fish (Higgins and others 1998). …”
Section: Introductionmentioning
confidence: 99%
“…Four species, Enterocytozoon bieneusi, Encephalitozoon intestinalis, Encephalitozoon hellem , and Encephalitozoon cuniculi , are responsible for causing the majority of microsporidian infections in humans [16,17]. Fumagillin and related compounds such as TNP‐470 and ovalicin appear to be among the most effective drug for treating microsporidiosis [4,5,8,9,16,17,20,21]. Fumagillin, TNP‐470, and ovalicin also inhibit angiogenesis by covalently binding to methionine aminopeptidase 2 (MetAP2) in endothelial cells [7,10,18,22].…”
mentioning
confidence: 99%